Improving methane yield of oil palm empty fruit bunches by wet oxidation pretreatment: Mesophilic and thermophilic anaerobic digestion conditions and the associated global warming potential effects. (1st December 2020) - Lee, Jonathan T.E.; Khan, Muhammad Usman; Tian, Hailin; Ee, Alvin W.L.; Lim, Ee Yang; Dai, Yanjun; Tong, Yen Wah; Ahring, Birgitte K.
Graphical abstract: Highlights: Lignocellulosic oil palm empty fruit bunches pretreated by wet oxidation method. OPEFB was anaerobically digested at mesophilic and thermophilic conditions. Thermophilic AD produced methane faster but at a lower yield compared to mesophilic. Pretreatment increased biomethane yield by up to 43% under optimal conditions. LCA of the impact on global warming potential revealed that the method was environmentally-friendly. Abstract: Palm oil production is a significant agricultural industry in the South East Asia region and the empty fruit bunch by-product OPEFB is a lignocellulosic biomass left after palm oil recovery, which has shown to be recalcitrant to bioconversion. Pretreatment experiments were carried out in this study to mitigate the recalcitrance of this material using oxygen assisted hydrothermal pretreatment (with 3–9% oxygen loading in the form of H2 O2 ) followed by batch anaerobic digestion at both mesophilic and thermophilic conditions. The optimal pretreatment for OPEFB was found to be with 6% oxygen at mesophilic condition resulting in 43% increase in methane yield over the control while at thermophilic conditions, the ultimate methane yield was ultimately lower, but received within a shorter time period. The gate-to-gate process was analyzed for global warming potential impacts and it was concluded that for the production of methane at the optimal condition resulted in the lowest greenhouse gas emissions (30% less than the control).